THE PEDAGOGICAL TRAINING OF FUTURE UNIVERSITY PROFESSORS AT ENGINEERING EDUCATION INSTITUTIONS - Evgeniy A. Korchagin; Rais S. Safin; Ilfak E. Vildanov; Runar N. Abitov (Высшее образование в России)
The key theme of the article is training of teachers of professional disciplines at secondary and higher education levels. There is presented a teacher training model for colleges, secondary technical schools and universities including different trajectories. Vocational and pedagogical training carried out according to these schemes ensures integration of psychological, pedagogical, and branch technology training. Thus we achieve an optimal combination of highly skilled teacher and expert in technology. The curriculum of pedagogical disciplines both in basic and elective parts are given.The pedagogical component in post-graduate education as a new level of education should be enhanced. The presented model of postBgraduate training assumes various educational trajectories provided with relevant curricula.The first trajectory is based on bachelor’s and master’s degree of teacher’s training major. The second one is recommended for training of teachers of professional disciplines on the basis ofbachelor’s and master’s degree in engineering. The curricula promote humanitarization of engineering education, integration of engineering and pedagogical knowledge, allow to enhance and deepen qualification of a future engineering university professor, increase the quality of engineering teacher training.